The Utilization Of Field Snails Into Soy Sauce Ingredients Enzymatically Regardless Of The Physical Quality (International Journal of Scientific Research and Management (IJSRM), 2024)
Rice soy sauce is a thick liquid made from snail meat juice . Soy sauce can be made in 2 ways, namely, traditionally/fermentation and by adding enzymes. Making soy sauce does not require a particular type of snail . In this research, we will study the use of rice snails to make rice snail sauce enzymatically. The aim of this research is to determine the effect of adding crushed pineapple tubers and fermentation time on the physical, chemical and organoleptic quality of the rice snail soy sauce produced. Proteolytic enzymes can break down and decompose proteins. Bromelain proteolytic enzymes can break down protein molecules into amino acids, enzymes that hydrolyze peptide bonds in the middle. This research used a completely randomized design (CRD) with a factorial pattern with 2 factors and 3 replications. The first factor was the addition of crushed pineapple tubers (10%), (15%), and (20%) and the second factor was the fermentation time (5.7 and 9 days). The results of this research show that when increasing the number of workers from 4 to 6 people, variable costs increase, but the number of rice snails produced increases , therefore the cost per bottle produced (marginal variable coast) decreases. The tendency to increase productivity often occurs when companies initiate production expansion. T et fire This is not the case if the company continues to expand production by continuing to increase the workforce employed.